Value enhancements of momentum strategies - Järvenpää, Santeri (My University, 2013)
The purpose of this thesis is to find out if the traditional momentum investing strategy can be enhanced by using the momentum life cycle and value multiples as performance boosters. In other words, the goal is to tie together both momentum and value-glamour anomalies. This anomaly connection is formed through the momentum life cycle hypothesis that was introduced by Lee and Swaminathan (2000). The success of this anomaly merger is measured by comparing if an investment strategy based on this anomaly combination is able to generate higher abnormal returns than the traditional momentum strategy. The sample data during 2000-2012 consists of the 30 stocks most suitable for purposes of this thesis, from the Helsinki Stock Exchange. The traditional momentum strategy is formed by using the widely accepted portfolio approach. Price-to-earnings and price-to-book ratios are used to detect different phases in the momentum life cycle of chosen stocks. Based on these phases early-strategy and late-strategy are formed as alternative strategies for traditional momentum strategy. Abnormal returns generated by these strategies are followed over 6, 12, 24, 36, 48 and 60 month holding periods. This thesis also takes a look at the performance of momentum investing in extreme market conditions, aka during the Financial Crisis. The results presented in this thesis show that positive price momentum evidently takes place in Helsinki Stock Exchange among previous winners. However, within this sample data negative price momentum was not observed among previous losers. This thesis also found out that price-to-earnings ratio is significantly more efficient as a tool to detect different phases in the momentum life cycle than price-to-book ratio. When the performances of different momentum strategies were compared, early-strategy showed superior performance if it was formed on the basis of price-to-earnings ratio. Excluding the time period of the Financial Crisis from data sample enhanced the performance and the significance levels of all investment strategies significantly.
Keywords: Momentum; value/glamour-anomaly; momentum life cycle; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|